Yukawa textures from non-invertible symmetries - Tatsuo Kobayashi; Hajime Otsuka; Morimitsu Tanimoto (Journal of High Energy Physics)
Abstract Phenomenological aspects of non-invertible symmetries, in particular the flavor structure of quarks and leptons, are studied. We start with a ℤ M discrete symmetry and gauge ℤ2 so as to obtain a non-invertible symmetry. We study which Yukawa textures can be derived from the non-invertible symmetries. Various textures can be realized and some of them cannot be realized by a conventional symmetry. For example, the nearest neighbor interaction texture as well as other interesting textures of quarks and leptons are obtained.